Life Cycle Inventory of Anaerobic Digestion at the Wastewater Treatment Plant of a Dairy Company - Muradin, Magdalena; Foltynowicz, Zenon (Studia Oeconomica Posnaniensia, 2017)
Biogas installations located on the premises of production plants are part of sustainable development policy, mainly because of their dual purpose. These plants are the ideal way to minimize various types of solid and liquid organic waste and furthermore to provide a stable source of renewable energy. Biogas produced in anaerobic digestion can be purified and injected directly to the grid, or what is more popular, subsequently combusted in a gas engine and converted into heat and power. The necessity to manage the huge amounts of effluent from milk production, mainly in the form of whey, forces dairies to constantly introduce new improvements related to wastewater treatment plants. In the investigated dairy plant, an anaerobic biogas reactor was launched, in order to improve the performance of the existing sewage plant. The main purpose of this modernization was the pollutant load reduction of dairy wastewater. The biogas made in this fermentation process was converted into thermal energy and used for heating the running biogas reactor as well as the production processes in the dairy. These studies were designed to evaluate the potential environmental impact of the anaerobic part of the upgraded wastewater treatment plant located at the dairy. The findings can be used in the decision-making process in other food processing plants where large amounts of organic wastewater are produced. In this research the Life Cycle Assessment (LCA) methodology was used. This paper presents the results of an environmental study on the second step of the LCA analysis. A Life Cycle Inventory (LCI) was used to identify the unit processes in the life-cycle of biogas production in the sewage plant at the dairy. All data were collected in a small local dairy company located in the Wielkopolska Region, Poland.